Pengaruh Komunikasi Interpersonal dan Disiplin Kerja Terhadap Kinerja Guru - Nilasari, Suyeti; Fitria, Happy; Rohana, Rohana (CV. Creative Tugu Pena, 2020)
This study determined the effect of interpersonal communication and work discipline on teacher performance. This study used quantitative methods. The sample of this research was 50 teachers of SMA Negeri 21 Palembang. Data were collected through questionnaires, documentation study, and observation. Data were analyzed using classical assumption test, multiple linear tests, coefficient of determination test and f-test. The results of this study indicate that there is partially and simultaneously significant effect of interpersonal communication and work discipline on the performance of teachers in SMA Negeri 21 Palembang. Keywords: Teacher’s Performance, Interpersonal Communication, Work Discipline